A Prototype Experimental Infectious Protien Vaccine - Ibrahim Mohamed Saeed Shnawa (Vaccines and Vaccine Interference, 2023)
The infectious protein agent” Prion” has shown to be of multi-epi-topic nature. Molecular mimicry of the protein epitope with the host epitope necessitate overcoming immune tolerance and avoidance of autoimmune reactions. The novel vaccine candidate epitope was the virulent associated epitope. The tempted experimental vaccine candidates were; Mono-epitopic, multi-epitopic, adjuvanated prion peptides, virus –like particle and DC loaded vaccine strategies in small and large mammalian laboratory animals. Among which VLP loaded vaccine was found to be promising in live prion –challenge mice model. Though till now there is no approved infectious protein vaccine both for human and animal welfare.